Elbow Grease - Cena, John; McWilliam, Howard, 1977- (New York : Random Hoouse, 2018)
Elbow Grease, a small, electric truck with a lot of gumption, enters the Monster Truck Grand Prix to prove to his brothers that he is just as capable as they are.
Keywords: Monster trucks -- Fiction; Trucks -- Fiction; Determination -- Fiction; Ability -- Fiction; Brothers -- Fiction